Analysis of Students' Learning Difficulties in Geometry and Measurement Learning at the Elementary School Level. - Marsya Grace Lady Waruwu; Naomi Meiati Sinaga; Aisyah Putri; Riska Inriani Zai; Arsya Medika Butar Butar; Sindi Miranda Br. Manullang; Doni Irawan Saragih (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to analyse the learning difficulties experienced by primary school students in geometry and measurement. This study was conducted through a literature review of various scientific articles published in the last five years that discuss difficulties, strategies, and solutions in geometry learning at the primary school level. The results of the study show that the main difficulties experienced by students include an inability to understand abstract concepts, limited spatial abilities, and difficulties in relating two-dimensional and three-dimensional shapes. In addition, a poor understanding of standard units and the use of measuring instruments are also major contributing factors. External factors such as traditional teaching methods, limited visual media, and minimal use of technology exacerbate these problems. Several solutions identified as effective include the application of the Realistic Mathematics Education (RME) approach, the use of visual media such as Geoboard and Augmented Reality, and gamification and contextual learning strategies. The results of this analysis have important implications for primary school teachers to improve their pedagogical competence and conceptual understanding in geometry and measurement learning, as well as to encourage more interactive, concrete, and meaningful learning innovations for students.